Playing, then and now – differences in time and elements of play from parents’ perspective - Rajović, Ranko; Ković, Vanja; Berić, Dragana (Annales Kinesiologiae, 2021)
The question how the general trend toward physical inactivity and sedentary behavior affects children’s capabilities and cognitive skills is becoming increasingly important. The aim of this study was to compare children’s play time with parents’ play time at their child’s age, as well as the elements of play. A survey was conducted among parents of children aged 6 to 8 years. The results of the survey, which was based on a sample of 37 parents, showed that a child nowadays spends more time playing at home (110 minutes/day on average compared to the 96 minutes/day their parents played as children) and, conversely, with a statistically significant difference, only half the time their parents did playing outside (96 minutes/day on average compared to the 157 minutes/day on average that their parents spent at the same age). We also found a statistically significant difference in screen time in children today (93 minutes/day on average), which is three times as much as it used to be in their parents at that age. Differences were also evident in activities involving elements of rotation, balance, and dynamic accommodation, with most children now spending 0-15 minutes/day compared to parents who used to spend an hour or more on similar activities. For activities based on fine motor skills, half of the children nowadays spend 15-30 minutes/day, whereas half of the parents used to spend an hour or more. The contemporary lifestyle that is highly sedentary can affect many aspects of children’s play. The paper discusses differences of play in the time dimension and possible consequences of such behavior for child development.